The Influence of Power Point Media on Student Motivation and Learning Outcomes - Partiyatun Partiyatun; Akhmad Jazuli (UM Purwokerto Press, 2023)
This study aims to determine the effect of the use of power point media on motivation and Indonesian language learning outcomes in rhyme writing skills for students in elementary schools in Kemranjen District, Banyumas Regency. The research method used is the Pre-Experimental Design with the One Group Pretest-Posttest Design. The population used was all fifth-grade students at SD Negeri Gugus Dwijo Utomo, Kemranjen District, while the sample was fifth grade students at SDN 1 Sibrama using random sampling technique. Data on learning outcomes used the results of students' Indonesian pretest and posttest. Data analysis used the t-test technique (independent sample t-test) with the SPSS 26 application. Data collection regarding learning motivation was carried out through observation and questionnaires. Retrieval of data using a questionnaire, the scale used is the Likert scale. The results of the analysis using the t-test technique (independent sample t-test) show that the significance value is 0.004 or <0.05, which means that Ho is rejected, which means that the power point has a positive effect on students' Indonesian learning outcomes. Meanwhile, the calculation on the Likert scale shows that the evaluation interval for the presence or absence of the influence of PowerPoint media on students' learning motivation is 75%. This indicates that 75% of students agree that learning using power point has a positive effect on students' learning motivation.